Effectiveness of Home Economics Learning Commons (HELCs) in Enhancing the Academic Performance of Grade 5 Learners: A Quasi-Experimental Research - Grace C. Endaya; Karen A. Manaig; Alberto D. Yazon; John Frederick B. Tesoro; Erica B. Tabuac (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
This quasi-experimental research design determined the effectiveness of the Home Economics Learning Commons (HELCs) in improving the academic performance of Grade 5 learners. It utilized the formative, summative, and post-tests as part of the research instruments. Match-pairing technique was used to determine the participants of the study. The said participants were the Grade 5 pupils from five different Cabuyao Elementary Schools. The comparison group consisted of students enrolled in the Online Distance Learning modality, while the experimental group consisted of students enrolled in the Modular Distance Learning modality. Based on the data gathered, it revealed that the mean scores in the formative test were high in both the comparison and experimental groups, while the mean scores in the summative test varied from 54-73% and were interpreted as average to near to mastery; and mean scores in the post-test ranged from 14-18.50%, considered as average to high. There was a substantial difference in the Pre-test and Post-test Mean Scores of the five participating schools' Comparison and Experimental Groups, according to the results of the Paired t-Test. Hence, the study concluded that there is a significant difference between the formative tests' mean scores of the two groups. Likewise, there is a significant difference between the post-test mean scores of the two groups. Lastly, there is a significant difference between the pre-test and post-test mean scores of each group. As a result, it was established that HELCs have a considerable positive effect on students' academic achievement.